2024 MHM Review Subforum Six Health Narratives and Cognitive Behavioral Research (The Journal of Medicine, Humanity and Media, 2024)
On July 11, 2024, Subforum Six of the 7th International Conference on Medicine, Humanity, and Media was held at Peking University's School of Journalism and Communication, focusing on "Health Narratives and Cognitive Behavioral Research." Co-chaired by Associate Professors Zhou Shuo and Gong Qian, the forum featured presentations from nine scholars exploring diverse aspects of health narratives and cognitive behavior. Topics included the impact of media framing on stigma surrounding depression, the dynamics of online health consultations, and the role of social media in supporting mental health. The discussions emphasized the importance of understanding narrative structures and communication strategies in promoting health and well-being.